Assessment Methods of Skills Needed in Technical and Vocational Education and Training for Renewed Hope in Nigeria - Sara, Habibu A.; Haruna, Rabiu; Rano , Habibu G. (International Journal of Educational and Psychological Sciences, 2024)
Technical, Vocational Education and Training has been recognized as a tool for poverty alleviation, youth empowerment and entrepreneurship opportunities. Hence, priority has been accorded to it globally and nationally. However, this type of training is not being properly assessed. This paper therefore, attempts to explain the assessment method of the skills needed in Technical, Vocational Education and Training for a renewed hope in Nigeria. In specific, the paper defined the concept of assessment in TVET, explained the need and types of assessment in TVET, the methods used in assessing TVET, the challenges for skills assessment in TVET, and at the end proffered some suggestions for a renewed hope in the system.